1977
DOI: 10.1111/j.1745-4557.1977.tb01001.x
|View full text |Cite
|
Sign up to set email alerts
|

THE ELIMINATION OF ENTERIC BACTERIAL PATHOGENS FROM FOOD AND FEED OF ANIMAL ORIGIN BY GAMMA IRRADIATION WITH PARTICULAR REFERENCE TO SALMONELLA RADICIDATION1

Abstract: Despite world‐wide severe underreporting of food‐transmitted disease of microbial origin, it is clear that the majority of such diseases is caused by enteropathogenic Enterobacteriaceae. Most of these are spread by foods of animal origin, consumed raw, or recontaminated subsequent to industrial or culinary heat processing. Radicidation with the help of gamma rays of carcasses or consumer size cuts presents a real solution to this problem. An ecologically based procedure for the estimation of the most probable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 142 publications
0
8
0
Order By: Relevance
“…Even though acid treatment has been advocated for use in poultry processing (Mountney & O'Malley 1965), as has freezing (Gunaratne & Spencer 1974) and freezing with acid (Olson et al 1981b), the stress effect of a pre-freezing exposure to chemicals has not been previously established. The current findings, although obtained using a chicken exudate system, may nevertheless have potential for eliminating Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though acid treatment has been advocated for use in poultry processing (Mountney & O'Malley 1965), as has freezing (Gunaratne & Spencer 1974) and freezing with acid (Olson et al 1981b), the stress effect of a pre-freezing exposure to chemicals has not been previously established. The current findings, although obtained using a chicken exudate system, may nevertheless have potential for eliminating Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations have sought to develop effective and suitable procedures for killing salmonellas of processed poultry. These include acid dips (Mountney & O'Malley 1965), irradiation (Idziak & Incze 1968;Mossel 1977), chlorination (Surkiewicz et al 1969;Morris & Wells 1970;Mead & Thomas 1973;Mead et al 1975), hot acid treatment (Juven et al 1974), freezing (Gunaratne & Spencer 1974), repeated freezethawing (Olson et al 1981a) and the Nurmi concept of protecting day-old chicks against salmonella colonization by establishing adult gut microflora (Pivnick & Nurmi 1982).…”
mentioning
confidence: 99%
“…Other studies showed that doses up to 10 kGy extended the shelf-life of chicken meat by 2 to 3 wk (Cho et al, 1985;Klinger et al, 1986). Mossel (1977) also reported that l-5 kGy irradiation doses could effectively destroy all Salmonellae on chicken carcasses. Tarkowski et al (1984) reported a reduction of 4 log numbers of Yersinia enterocolitica and Campylobacter jejuni on raw meat irradiated with up to 1.5 kGy dose.…”
Section: Introductionmentioning
confidence: 95%
“…However, few published studies have tested this concept. Adequate data exist on salmonellae as contaminants of fresh or frozen poultry to conclude that the limiting factors for the irradiation of this product are more organoleptic than microbiological (Mulder et al 1977;Mossel 1977). Food irradiation is appropriate for the control of Aeromanas hydrophila (Palumbo et al 1986) Cumpylobacter jejuni (Lambert and Maxcy 1984) and Lysteriu monocytogenes (Huhtanen et al 1989).…”
Section: Extension Of Shelf-life and Elimination Of Bacterial Pathogementioning
confidence: 97%